Symmetrized solutions for nonlinear stochastic differential equations - G. Adomian; L. H. Sibul (International Journal of Mathematics and Mathematical Sciences)
Solutions of nonlinear stochastic differential equations in series form can be put into convenient symmetrized forms which are easily calculable. This paper investigates such forms for polynomial nonlinearities, i.e., equations of the form Ly+ym=x where x is a stochastic process and L is a linear stochastic operator.